2017
DOI: 10.1021/acs.langmuir.7b03135
|View full text |Cite
|
Sign up to set email alerts
|

Single Layer Surface-Grafted PMMA as a Negative-Tone e-Beam Resist

Abstract: One of the important challenges in electron beam lithography is nanofabrication on nonflat or irregular surfaces. Although spin coating is the most popular technique for resist coating, it is not suitable for nonflat, irregular substrates because a uniform film cannot be achieved on those surfaces. Here, it is demonstrated that single layer surface-grafted PMMA can be used as a negative-tone e-beam resist, and it can be applied to nonflat, irregular surfaces as well as flat, conventional surfaces. Although it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There was a dose shift from 10 μC cm –2 to approximately 40 μC cm –2 . However, it is clear that the thiol–ene click-assisted resist system can effectively enhance the low sensitivity confinement since the commonly used electron beam resists such as poly­(methyl methacrylate) (PMMA) and hydrogen silsesquioxane (HSQ) , require doses generally above 150 μC cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…There was a dose shift from 10 μC cm –2 to approximately 40 μC cm –2 . However, it is clear that the thiol–ene click-assisted resist system can effectively enhance the low sensitivity confinement since the commonly used electron beam resists such as poly­(methyl methacrylate) (PMMA) and hydrogen silsesquioxane (HSQ) , require doses generally above 150 μC cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…[18] Lithographic processes that use PMMA for negative image formation are of continued interest due to their potential to realize structures of higher resolution, as a positive tone process suffers from structures that shrink due to overdeveloping (for example). [17][18][19][20] The hardness of highly irradiated PMMA can approach 10-20 GPa for electron fluences that approach 10 15 cm À2 , implying that defined features can retain their shape. [21] According to simulations, the interaction volume for helium ion beams is much smaller than the interaction volume for ebeams, and helium ion beams become more collimated as the landing energy increases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Lithographic processes that use PMMA for negative image formation are of continued interest due to their potential to realize structures of higher resolution, as a positive tone process suffers from structures that shrink due to overdeveloping (for example). [ 17–20 ] The hardness of highly irradiated PMMA can approach 10–20 GPa for electron fluences that approach 10 15 cm −2 , implying that defined features can retain their shape. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it has been reported that e-resist with low-viscosity and low-surface-tension can be coated on non-planar surfaces [26] by spin coating. Besides spin coating, various other methods have been demonstrated to deposit resist films on non-planar surfaces such as spray coating [27], Langmuir-Blodgett (LB) technique [28], float coating [8], monolayer brush [29][30][31], dip coating [30,32] and ice lithography (IL) [33][34][35][36]. However, most of these methods exhibit some major issues such as non-uniformity, ultra thin-films, reproducibility and extremely low sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Well-known examples are magnetic force microscopy [8,9], tip-enhanced Raman spectroscopy [10], near-field optical focusing [11], scanning single-electron transistor microscopy [12] and scanning thermal microscopy (SThM) [13][14][15][16][17][18][19][20][21][22][23][24][25] that demand nanofabrication on 3D atomic force microscopy (AFM) probes. Recently, a considerable amount of literature has been published on EBL for creating nanostructures on irregular surfaces [26][27][28][29][30][31][32][33][34][35][36][37][38]. However, it is still very challenging to perform EBL on non-planar, 3D architectures because of the lack of uniformity and reproducibility of electron sensitive resist (e-resist) films on the substrates.…”
Section: Introductionmentioning
confidence: 99%